2018
DOI: 10.1111/exd.13442
|View full text |Cite
|
Sign up to set email alerts
|

Human tissue inhibitor of metalloproteinases‐1 improved wound healing in diabetes through its anti‐apoptotic effect

Abstract: Impaired wound healing accompanies severe cell apoptosis in diabetic patients. Tissue inhibitor of metalloproteinases-1 (TIMP-1) was known to have effects on promoting growth and anti-apoptosis for cells. We aimed to determine the actual levels of TIMP-1 and cell apoptosis in: (i) the biopsies of diabetic and non-diabetic foot tissue and (ii) the human fibroblasts with or without treatments of advanced glycation end-products (AGEs). Next, we aimed to determine the improved levels of cell apoptosis and wound he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 34 publications
1
23
1
1
Order By: Relevance
“…Okamoto et al Dentinogenic effect of TIMP1 International Endodontic Journal, 52, 1051-1062, 2019 may have a cytoprotective effect and induce cell proliferation during the wound healing process. These results are consistent with those of a report of TIMP1 using other cells (Lao et al 2017).…”
Section: Groupsupporting
confidence: 94%
“…Okamoto et al Dentinogenic effect of TIMP1 International Endodontic Journal, 52, 1051-1062, 2019 may have a cytoprotective effect and induce cell proliferation during the wound healing process. These results are consistent with those of a report of TIMP1 using other cells (Lao et al 2017).…”
Section: Groupsupporting
confidence: 94%
“…Diabetic ulcers are the most common chronic wounds developed in the patients with diabetes, usually on the feet. It has been reported that up to 15% of diabetic patients suffer from nonhealing foot ulcers, which mainly account for 84% of diabetes‐related leg amputations …”
Section: Introductionmentioning
confidence: 99%
“…TIMP1, also known as tissue inhibitor of metalloproteinases-1, is a multifunctional protein that promotes cell proliferation and exhibits anti-apoptotic functions ( 37 , 38 ). A recent study reported that TIMP1 knockdown using short hairpin RNA in gemcitabine (GEM)-resistant pancreatic ductal adenocarcinoma cells enhanced GEM sensitivity and reversed chemoresistance by inducing cell apoptosis ( 39 ).…”
Section: Discussionmentioning
confidence: 99%